Interplay of light and nitrogen for plant growth and development - Chenlong Guan; Dong Zhang; Chengcai Chu (Crop Journal)
Light and nitrogen (N) are two critically environmental factors essential for plant survival, as they constitute the fundamental molecular framework of plant cells and significantly influence patterns of plant growth and development. Light is the driving force behind photosynthesis, a process that converts light energy into chemical energy stored as sugars. Additionally, light acts as a direct signal that can modulate plant morphogenesis and structural development. Nitrogen, as the most crucial mineral nutrient for plants, is a component of numerous biomolecules. It also functions as a signaling molecule, regulating plant growth and development. Moreover, light and nitrogen directly regulate the balance of carbon (C) and N within plants, affecting numerous biochemical reactions and various physiological processes. This review focuses on the interactions between light and nitrogen in physiological, metabolic, and molecular levels. We will also discuss the regulatory networks and mechanisms through which light and nitrogen influence C and N absorption and metabolism in plants.